Physical Properties of Zinc Compounds Obtained by Electrolytic Method - A.V. Lysytsya; M.V. Moroz; B.D. Nechyporuk; B.P. Rudyk; B.F. Shamsutdinov (Фізика і хімія твердого тіла, 2021)
The influence of the chemical composition of the electrolyte and its temperature on the process of sythesis of nanosized zinc compounds by electrolytic method using zinc electrodes was investigated. X-ray studies have been conducted and its results were used to determine the composition of the obtained nanocrystal samples and its dimensioning using the Debye and the Williamson Hall methods. Comparisons of the results of dimensioning of nanocrystals by both methods were made. Also discussed the possibilities of synthesis of nanoparticles of zinc oxide, zinc sulfide and hydrozincite by electrolytic method. It is shown, that depending on the electrolyte composition, nanocrystals of zinc oxide, zinc sulfide, hydrozincite or their mixture are obtained. The effect of thermal annealing on the samples composition and dimensioning was investigated.